2013
DOI: 10.1016/j.jval.2013.03.568
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of pregabalin for the treatment of neuropathic pain in Colombia

Abstract: Kong SLE patients compared to standard care. METHODS: A lifetime microsimulation model was adapted with epidemiological and cost data from Hong Kong. The model compares the use of belimumab against standard care and incorporates the BLISS-52 and BLISS-76 trial data for the short term outcomes within one year, while long-term outcomes were based on a natural history model developed using the Johns Hopkins Lupus registry. The natural history model describes the relationship between disease activity and other cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Table 1 provides an overview of cost per patient data. Studies reported different perspectives when estimating costs such as social perspective (n = 3), 49 , 59 , 60 third-party payer perspective (n = 1) 64 and the public perspective (n = 1). 65 Out-of-pocket expenses were reported in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides an overview of cost per patient data. Studies reported different perspectives when estimating costs such as social perspective (n = 3), 49 , 59 , 60 third-party payer perspective (n = 1) 64 and the public perspective (n = 1). 65 Out-of-pocket expenses were reported in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Most economic studies were of adequate quality. However, of the eight studies with economic study designs, 49–52 58–65 only one study 60 used the discount rate, while none of the studies adjusted their cost estimates based on inflation rates. Four studies did not report any comparator, and three studies did not report any estimation of direct or indirect costs.…”
Section: Resultsmentioning
confidence: 99%